Social distancing cut down the prevalence of acute otitis media in children - Yu, Huiqian; Gu, Dantong; Yu, Fangzhou; Li, Qingzhong (Frontiers in Public Health, 2023)
Objectives To evaluate the additional, unintended benefits of social distancing in cutting down the prevalence of acute otitis media (AOM) in children, especially during coronavirus disease 2019 (COVID-19) periods. Methods The daily outpatient attendance of AOM for childhood (from 6 months to 12 years) was compared in the tertiary hospital in Shanghai during pre-COVID-19 and COVID-19 year. Results A total of 24,543 AOM cases were included from 2015 to 2020. When age was taken into account, children in kindergarten (aged 4–6) constitute 66.2% (16,236/24,543) of all case, followed by primary school students (6,441/24,543, 26.2%) and preschoolers <3 years old (1,866/24,543, 7.6%). There was an estimated 63.6% (54.32–70.36%) reduction in the daily outpatient attendance of AOM associated with the introduction of social distancing in 2020 (COVID-19 year). The epidemic trend of AOM in 2015–2019 was characterized by seasonal fluctuations, with highest incidence in December (18.8 ± 0.5%) and lower in February (4.5 ± 0.2%), June (3.7 ± 0.7%) and August (3.5 ± 0.5%). And distribution characteristics of different ages in COVID-19 period broadly in line with that in non-pandemic period. Conclusion Seasonal fluctuation in the prevalence of AOM was observed in pre-COVID-19 period (2015–2019), with a peak in winter and a nadir in summer. The >50% drop of outpatient attendance of AOM in 2020 (COVID-19 year) suggest that social distancing, mask effects and good hand hygiene can significantly reduce the incidence of AOM, which provides a preventive and therapeutic point of view for AOM.